Utility of post-procedural anticoagulation after primary PCI for STEMI: insights from a pooled analysis of the HORIZONS-AMI and EUROMAX trials. Issue 7 (1st October 2017) - Ducrocq, Gregory; Steg, Philippe Gabriel; van't Hof, Arnoud; Zeymer, Uwe; Mehran, Roxana; Hamm, Christian W; Bernstein, Debra; Prats, Jayne; Deliargyris, Efthymios N; Stone, Gregg W
Abstract: Background: Many sites routinely continue anticoagulation after primary percutaneous coronary intervention in patients with ST-segment elevation myocardial infarction (STEMI), despite an unclear benefit–risk ratio. We evaluated the impact of this strategy on 30-day outcomes from a pooled patient-level database of two large primary percutaneous coronary intervention trials. Methods: EUROMAX and HORIZONS-AMI were both multicentre, international randomised trials comparing bivalirudin to heparin with or without glycoprotein IIb/IIIa inhibitors in patients with STEMI undergoing primary percutaneous coronary intervention. Outcomes at 30 days were analysed according to the use of post-procedural anticoagulation (unfractionated or low-molecular-weight heparins or fondaparinux) outside of the catheterisation laboratory. Results: Among 5239 patients undergoing primary percutaneous coronary intervention, 2153 (41.1%) received post-procedural anticoagulation. After adjusting for differences in baseline variables, there were no differences in the 30-day rates of adverse ischaemic events between patients without versus with post-procedural anticoagulation: adjusted odds ratio for major adverse cardiac events 0.80; 95% confidence interval 0.60–1.07; P =0.14; adjusted odds ratio for stent thrombosis 0.82; 95% confidence interval 0.55–1.24; P =0.35; adjusted odds ratio for death 1.07; 95% confidence interval 0.69–1.66; P =0.77. Conversely, protocol-defined major bleeding was decreased without post-procedural anticoagulation: adjusted odds ratio 0.74; 95% confidence interval 0.58–0.94; P =0.01. Similar results were observed for Thrombolysis In Myocardial Infarction major and minor bleeding. Conclusions: In this large STEMI database, a substantial proportion of primary percutaneous coronary intervention patients received post-procedural anticoagulation, which in turn was associated with higher bleeding rates without any reduction in ischaemic events. Therefore, routine post-procedural anticoagulation after primary percutaneous coronary intervention seems to have an unfavourable benefit–risk profile and should be avoided unless a well-established indication is present. Clinical Trial Registration: ClinicalTrials.gov, EUROMAX Identifier NCT01087723; HORIZONS Identifier NCT00433966